Framework Nucleic Acids: A Paradigm Shift in Transdermal Drug Delivery. (October 2019) - Wiraja, Christian; Yeo, David C.; Xu, Chenjie
Transdermal drug delivery (TDD) provides a direct drug administration route bypassing gastrointestinal and liver metabolism. Until now, topical nanocarriers responsible for efficient TDD are predominantly polymeric or lipid based. The size-dependent skin penetration ability of framework nucleic acids (FNAs) has recently been reported, along with their efficacy in delivering doxorubicin for skin melanoma therapy. This commentary is to highlight the paradigm shift of nucleic acid delivery from being a cargo moiety to serving as a drug carrier instead. Further development directions to maximize the potential of FNAs for TDD are also discussed.